Possibilities for a liberating pedagogy : a critical exploration of an Icelandic course for asylum seekers - Evan Jett Lewis 1993- (2019)
Second-language learning courses that are often offered to asylum seekers provide a unique opportunity for a pedagogy of critique to be implemented. However, there is essentially no existing research in Iceland, and very little internationally, that considers the practicality of implementing a pedagogy of critique within second-language classrooms for asylum seekers. Moreover, the experiences of teachers and students within these programs have not been considered to the degree that allows for a genuine exploration of what these courses are like and how critical pedagogy could fit into their existing structures. This qualitative case study seeks to develop a deep understanding of the Red Cross’ “Icelandic for Asylum Seekers” course through the lens of critical pedagogy. My goal is to contribute to the knowledge regarding education for asylum seekers in Iceland, as well as to the broader field of critical pedagogy and its practical applications within second-language learning programs geared towards this group of people. The theory of critical pedagogy functioned as a framework that informed my approach to this research as well as a lens through which I analyzed my data. The primary methods of data collection used were participant observations, semi-structured, in-depth interviews of students and teachers, field notes, and to a lesser extent document analysis. The specific methods utilized in this research were selected to allow for a more comprehensive understanding of the program vis-á-vis observed classroom practices, teacher and student dynamics, and the individual experiences and perceptions of teachers and students within the program. Thematic analysis was used to make sense of the data collected. These methods of data collection and analysis allowed for a better understanding of the specific areas of tension that hindered the asylum seekers students from experiencing a liberating learning experience. The findings suggest that there were three major areas of tension that hindered the students from ...